IMPLEMENTASI PERMAINAN TRADISIONAL CONGKLAK DALAM MENGEMBANGKAN KEMAMPUAN BERHITUNG ANAK DI GANG BERSAMA, MEDAN SELAYANG - Heka Maya Sari Sembiring; Rizki Bastanta B. Manalu; Fuan Felix; Patrika Zein Sirait; Rahul Pandiangan (ASOSIASI IDEBAHASA KEPRI, 2026)
This community service activity aimed to enhance elementary school students’ numeracy skills through the implementation of the traditional game congklak in Gang Bersama, Medan Selayang. Congklak was chosen as a learning medium because it combines educational, social, and cultural values while aligning with the characteristics of children who enjoy playing and learning through direct experience. The activity was carried out using short lectures, demonstrations, hands-on practice, and mentoring. The participants consisted of 5–10 elementary school students aged 7–12 years who actively engaged in the game. The results showed significant improvement in students’ counting skills, particularly in basic addition and subtraction, as well as increased accuracy, concentration, and self-confidence. Students also demonstrated high enthusiasm, better understanding of game rules, and positive attitudes such as discipline, cooperation, and sportsmanship. Beyond cognitive benefits, the activity raised community awareness of the importance of traditional games as both educational tools and cultural heritage. Therefore, congklak proved to be an effective, enjoyable, and culturally contextual medium for developing numeracy skills among elementary school students.